2011
DOI: 10.1144/0036-9276/01-410
|View full text |Cite
|
Sign up to set email alerts
|

Regional geochemical comparisons from the Lower Palaeozoic, Southern Uplands–Down-Longford terrane in Northern Ireland and Scotland

Abstract: SynopsisNewly-acquired regional geochemical data for the Down-Armagh (Northern Ireland) sector of the Southern Uplands -Down-Longford terrane are assessed by comparison with the equivalent dataset for southern Scotland. Despite the much thicker glacigenic cover to the Down-Armagh bedrock, the principal geochemical lineaments identified in the Southern Uplands are still apparent. Patterns of element distribution emphasise the continuity of structure and stratigraphy between the two regions, with Cr, Zr, Sr, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…They also mention the contrasting absence of such haloes around the Criffel and Newry plutons, and the Mournes granite, which intrude mainly Hawick Group strata. Breward et al (2011) were unable to categorically ascribe these features to original geochemical differences in the greywackes or to the intrusion process of the granite.…”
Section: Significance Of Elevated Cu Within Gold Alloysmentioning
confidence: 98%
See 1 more Smart Citation
“…They also mention the contrasting absence of such haloes around the Criffel and Newry plutons, and the Mournes granite, which intrude mainly Hawick Group strata. Breward et al (2011) were unable to categorically ascribe these features to original geochemical differences in the greywackes or to the intrusion process of the granite.…”
Section: Significance Of Elevated Cu Within Gold Alloysmentioning
confidence: 98%
“…A possibility then is that copper has been introduced from a concealed magmatic source. Breward et al (2011) mention the prominent haloes of Pb-Zn-As and lesser Cu enrichment in stream sediments (and therefore bedrock) around the Loch Doon and Cairnsmore of Fleet plutons which intrude Gala Group strata (Fig. 1).…”
Section: Significance Of Elevated Cu Within Gold Alloysmentioning
confidence: 99%
“…Much of the bedrock of the north of Ireland is overlain and obscured by glacial deposits and peat, but the geochemistry of soils and sediments has nevertheless been shown to be representative of bedrock. Breward et al (2011) compared the stream sediment geochemistry for the Tellus survey with that for sediments overlying equivalent Lower Palaeozoic bedrock in southern Scotland. Despite the much thicker cover overlying the bedrock in the Down-Armagh area of Northern Ireland, the principal geochemical lineaments identified in Scotland are still apparent, with patterns of the distribution of several elements demonstrating the continuity of structure and stratigraphy between the two regions.…”
Section: Geological Mappingmentioning
confidence: 99%
“…Stone et al (1999 identified two element assemblages as being of particular value in tracking geologicallycontrolled changes in sediment composition: the basic-ultrabasic elements (Cr-Ni-Mg-VTi), and the feldspar association (Rb-Sr-K-Ba), both of which had potential as lithostratigraphical mapping surrogates. Breward et al (2011) were able to extend the element distribution patterns seen in the Southern Uplands westward into the DownLongford inlier, Ireland, utilising similar geochemical data acquired there as part of the TELLUS project. However, the direct spatial associations between the patterns of element distribution in stream sediment and changes in the underlying bedrock outcrop do not necessarily mean that the two media have the same compositions.…”
Section: Lithostratigraphy and Provenancementioning
confidence: 99%